Evaluation of Chemical Properties, Biological Activities and Ethnomedicinal uses of Cladostemon kirkii - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Cladostemon kirkii (Oliv.) Pax & Gilg is a shrub or a small tree widely used as traditional medicine in tropical Africa. This study is aimed at evaluating the chemical properties, biological activities and ethnomedicinal uses of C. kirkii. Results of the current study are based on data derived from several online databases such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as scientific publications, books, dissertations, book chapters and journal articles. The articles published between 1960 and 2019 were used in this study. This study revealed that the bark, leaf, root and stem infusion and/or decoction of C. kirkii are mainly used as traditional medicines for boils, colds, gastro-intestinal problems, hypertension, ophthalmia, rheumatism, sexual dysfunction, abdominal pains, sexually transmitted infections, sores and wounds. Phytochemical compounds identified from the species include mearnsitrin, myricitrin, kaempferol-5-rhamnoside, kaempferin, kaempferol 3-gluco-7-rhamnoside, quercetin 3,7-dirhamnoside, quercetin 3-gluco-7-rhamnoside, choline, 3-hydroxyprolinebetaine and tetramethylammonium. Cladostemon kirkii should be subjected to detailed phytochemical, pharmacological and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological properties.